MUC1 and glycan probing of CA19-9 captured biomarkers from cyst fluids and serum provides enhanced recognition of ovarian cancer - Shamima Afrin Ruma; Rufus Vinod; Shruti Jain; Kaisa Huhtinen; Johanna Hynninen; Janne Leivo; Kim Pettersson; Karin Sundfeldt; Kamlesh Gidwani (Scientific Reports)
Abstract Glycosylation changes of circulating proteins carrying the CA19-9 antigen may offer new targets for detection methods to be explored for the diagnosis of epithelial ovarian cancer (EOC). Search for assay designs for targets initially captured by a CA19-9 antigen reactive antibody from human body fluids by probing with fluorescent nanoparticles coated with lectins or antibodies to known EOC associated proteins. CA19-9 antigens were immobilized from ascites fluids, ovarian cyst fluids or serum samples using monoclonal antibody C192 followed by probing of carrier proteins using anti-MUC16, anti-MUC1 and, anti STn antibodies and seven lectins, all separately coated on nanoparticles. Compared to reference CA19-9 and CA125 immunoassays, nanoparticle aided detection using MUC16, Ma695 and STn antibodies and lectin WGA provided, both separately and combined, improved discrimination of EOC and borderline cancers from benign samples when applied to 60 cyst fluid specimens. When applied to a panel of 44 serum samples (EOC N = 24, healthy and benign samples N = 20) two assays, CA19-9Ma695 and CA19-9MUC1, stood out with equally superior separations (p-values < 10–8) of the two groups compared to conventional CA19-9 immunoassay (p-value 0.03).Eu+3 -NP based CA19-9MUC16, CA19-9Ma695, CA19-9STn and CA19-9WGA show promise for improved EOC detection when applied to ascites & cyst fluids. When applied to circulation-derived samples, the two MUC1 based assays, CA19-9Ma695 and CA19-9Ma552 outperformed other assay constructs. Our results call for further validation in larger EOC cohorts preferentially with early stage ovarian cancers and all major histotypes against commonly occurring benign conditions.